A model for evaluating realism, interactivity and the feeling of presence in virtual reality: scientific diffusion in 360-degree videos on YouTube (Research, Society and Development, 2022)
Virtual reality (VR) is recognized as a technology with great immersive capacity, that is, it makes the viewer feel as if they are experiencing everything first-hand. Through the literature, it was possible to observe that immersion in VR is directly linked to how realism, interactivity and the feeling of presence are constructed. Based on the specific characteristics of each of these three elements, an analysis card was created to verify how 360-degree videos work with those items. To test this card, in a second moment, scientific diffusion videos made in 360º, which are in Portuguese and available on YouTube, were analyzed in the study case. The choice for scientific diffusion was due to the fact that, according to the literature, it needs to find new and more creative ways of approaching the public, and VR, because of its immersive nature, shows great potential in this regard. In the analysis it was observed that there is no uniformity in the way in which realism, interactivity and the sense of presence are worked in the selected videos.